EFFECT OF THE IMPLEMENTATION OF ASEAN CHINA FREE TRADE AREA (ACFTA) ON THE IMPORT OF BATIK TEXTILE PRODUCTS IN INDONESIA YEAR 1998 - 2014 - Kurniawan, Yani; Syah, Tantri Yanuar Rahmat (Aktualita Manajemen, 2016)
AbstractACFTA affect many economic trade sectors in Indonesia either from the Import, Export as well as the states finances and its policies. The objective of free trade around the world is more on looking at the benefits to both countries that entered into the agreement. The ACFTA will influence competitiveness and comparative advantage among members of ASEAN in the textile, one of the Textile products become an image of Indonesian nation culture, it is call Batik, as it continues to spread worldwide and is recognized as a primary need that should be preserved our country. However, much of the existing literature on ACFTA seeks to provide qualitative estimates of the overall effect of ACFTA on ASEAN and China. In line with this, this research aims to determine the effect of Batik Imports from China that become bigger after the enactment of ACFTA. This study examines the value of Batik Textile Imports from 1998 to 2014. To see the implementation of ACFTA since 2007, the researchers divided the value of imports into two periods: 1998-2006 for before ACFTA and 2007-2014 for after ACFTA. This study uses a difference test method of non-parametric Mann Whitney. The results indicate that the value of batik imports from China after the ACFTA is greater than before ACFTA with significant value of <0.05.Keywords: ACFTA, Import, Batik Textile